Enhancement of sugar beet seed germination, plant growth, performance and biochemical components as contributed by algal extracellular products - Aly, M. H. A.; Abel El-All, Azza A. M.; Mostafa, Soha S. M. (2008)
The combination of seed-presoaking and foliar application method significantly increased leaves chlorophyll contents, as well as, nitrogen, phosphorus and potassium percentages in roots over the control in both seasons.
Includes reference.
Summary in arabic.
1
Keywords: Sugar beet -- Seeds; Sugar beet -- Preharvest sprouting; Plant regulators; Germination; Plant regulators -- Foliar application; Beets; Beta vulgaris